2002
DOI: 10.1034/j.1600-0714.2002.310207.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fluconazole‐resistant strains ofCandida albicansin otherwise healthy outpatients

Abstract: Our results showed that the presence of fluconazole-resistant strains of C.albicans does not appear to be prevalent among healthy outpatients furthermore, in vitro antifungal susceptibility testing does not always predict successful therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…On the other hand, C. krusei and C. glabrata were resistant to this drug. These results are consistent to those reported by several authors (8,23,26). On the other hand, itraconazole demonstrated a surprisingly low efficacy against C. albicans isolates.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, C. krusei and C. glabrata were resistant to this drug. These results are consistent to those reported by several authors (8,23,26). On the other hand, itraconazole demonstrated a surprisingly low efficacy against C. albicans isolates.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, fluconazole was speculated to show poor efficacy against Candida isolates, especially C. albicans isolates, as 56.7% of these isolates demonstrated resistance against fluconazole; this finding was not in consistence with previous studies. However, many studies have reported a lower incidence of fluconazole resistance, compared to the present study [22, 23]. In this regard, according to a study by Yenisehirli et al ., the resistance of C. albicans isolates to ketoconazole and fluconazole was estimated at 32% and 34%, respectively [13].…”
Section: Discussioncontrasting
confidence: 51%
“…1 A recent American study has demonstrated no fluconazole-resistant strains of C. albicans in an otherwise healthy population with oral candidosis following treatment with fluconazole. 12 Despite the availability of fluconazole as an overthe-counter medicine, there is not yet any evidence that this has been associated with an increase in resistance; however, there is no national surveillance scheme capable of detecting this. 13 Other antimicrobial agents are available for topical administration in oral candidosis in the form of mouthwashes.…”
Section: Discussionmentioning
confidence: 99%